Botulism (Veterinary Science, 2017)
Botulism is a neuroparalytic affection caused by ingestion oftoxins produced by Clostridium botulinum, a gram positive bacterium,anaerobic spore-forming, which are widely distributedin nature, soil and sediments of lakes and seas. It has been describedseven neurotoxins (A to G); the C most commonly foundin small animals. In dogs, the disease mainly occurs by ingestionof preformed toxin present in spoiled food or rotting carcasses.The neurotoxin type C cause blockage of acetylcholine receptorsat neuromuscular junction, generally from hours to days afteringestion. The affected dogs have ascending flaccid paralysis ofthe skeletal muscles, although the sensitivity and awareness aremaintained. Initial diagnosis is carried out through the historyof the animal as well as clinical manifestations. The standardtechnique for definitive diagnosis is intraperitoneal inoculationof blood serum of suspected animals in mice. Supportive care isessential to recovery. The prognosis is good if there is no developmentof secondary infections or other complications. The recoveryis complete after a period of 2 to 3 weeks. In more severecases, death can occur due to paralysis of the respiratory muscles.The prevention of the disease in dogs is based on restrictingthe consumption of spoiled food or rotting carcasses
Keywords: botulism; Clotridium botulinum; neurotoxin; flaccid paralysis; dogs